2020
DOI: 10.1210/clinem/dgaa023
|View full text |Cite
|
Sign up to set email alerts
|

Brain Differences in the Prefrontal Cortex, Amygdala, and Hippocampus in Youth with Congenital Adrenal Hyperplasia

Abstract: Context Classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency results in hormone imbalances present both prenatally and postnatally that may impact the developing brain. Objective To characterize gray matter morphology in the prefrontal cortex and subregion volumes of the amygdala and hippocampus in youth with CAH as compared to controls. Design … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 47 publications
0
39
1
Order By: Relevance
“…Patients were treated either with hydrocortisone, prednisolone, or dexamethasone. Also here, reductions in the volumes of the prefrontal cortex, amygdala, and hippocampus were observed [ 48 ].…”
Section: Long-term Follow-up and Perspectivementioning
confidence: 88%
See 2 more Smart Citations
“…Patients were treated either with hydrocortisone, prednisolone, or dexamethasone. Also here, reductions in the volumes of the prefrontal cortex, amygdala, and hippocampus were observed [ 48 ].…”
Section: Long-term Follow-up and Perspectivementioning
confidence: 88%
“…More recent observational studies from the UK, USA, and Sweden regarding brain morphology in patients with CAH have revealed that patients show reductions in cortical and limbic regions of the brain that are important for the working memory [ 45 , 47 , 48 ]. This new evidence points to the fact that alterations in brain structure and possibly also in the functional organization of the brain may underlie the cognitive changes [ 45 , 47 , 48 ]. In the UK study [ 45 ], patients with CAH showed reductions in volumes of the right hippocampus, left amygdala, bilateral thalamus, cerebellum, and brainstem.…”
Section: Long-term Follow-up and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Details of the in vivo amygdala probabilistic atlas construction, validation, estimates of individual differences, and comparison with previous atlas’ have been previously reported ( Tyszka and Pauli, 2016 ; Pauli et al, 2018 ). As previously published ( Herting et al, 2020 ), we adapted this technique to allow for each youth’s image to be registered to the CIT168 atlas using a B-spline bivariate symmetric normalization (SyN) diffeomorphic registration algorithm from ANTs version 2.2 ( Avants et al, 2007 ). Applying the inverse diffeomorphism mapped the CIT168 probabilistic atlas labels to the individual space of each participant, yielding probabilistic ROIs for left and right total amygdala and the following nine subregions: lateral nucleus (LA); dorsal and intermediate divisions of the basolateral nucleus (BLDI); ventral division of the basolateral nucleus and paralaminar nucleus (BLVPL); basomedial nucleus (BM); central nucleus (CEN); cortical and medial nuclei (CMN); amygdala transition areas (ATA); amygdalostriatal transition area (ASTA); and anterior amygdala area (AAA).…”
Section: Methodsmentioning
confidence: 99%
“…Serial radiographs of the left hand and wrist were obtained for bone age assessment as part of standard care in youth with CAH, and as part of an evaluation of short stature in otherwise healthy control youth. A smaller proportion of CAH and control participants had x-rays obtained as part of different research studies (Kim et al, 2015;Herting et al, 2020).…”
Section: Methodsmentioning
confidence: 99%